2019
DOI: 10.1002/kin.21301
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of model compound of algal biomass

Abstract: This contribution investigates thermal decomposition of leucine, as a representative model compound for amino acids in algal biomass. We map out potential energy surface for a wide array of unimolecular and self‐condensation reactions operating in the decomposition of leucine. Decarboxylation and dehydration of leucine ensues by eliminating CO2 and –OH, respectively, from the –COOH group attached to the α‐carbon. The molecular channel for deamination involves cleavage of NH2 from α‐carbon of leucine. The activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…The decarboxylation and deamination channels entail activation barriers of 282.1 (TSM2) and 273.9 kJ/mol (TSM3), respectively. These values are in accord with analogous values previously computed for leucine at 299.5 and 278.8 kJ/mol, respectively, computed at the CBS-QB3 . It is unlikely that these two channels will significantly participate in the initial degradation of the Ser compound.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The decarboxylation and deamination channels entail activation barriers of 282.1 (TSM2) and 273.9 kJ/mol (TSM3), respectively. These values are in accord with analogous values previously computed for leucine at 299.5 and 278.8 kJ/mol, respectively, computed at the CBS-QB3 . It is unlikely that these two channels will significantly participate in the initial degradation of the Ser compound.…”
Section: Resultssupporting
confidence: 90%
“…For instance, deamination reactions are prominent in the case of energy crops and lignocellulose when compared to sludge and microalgae. We have illustrated in a previous study that the formation of the experimentally major observed products from pyrolysis of leucine amino acid takes place via bimolecular reactions . Such reactions typically occur in the condensed medium prior to evaporation.…”
Section: Introductionmentioning
confidence: 97%
“…The potential barriers of this path (304.85 and 256.46 kJ mol À1 ) are similar to those observed for leucine. 37 The initial reaction step is ratedetermining, and the energy barrier is not high, which further conrms that path VII-1 plays an important role in Phe pyrolysis.…”
Section: Nh 3 Formation Pathsmentioning
confidence: 96%
“…18,19 Spirulina is a marine algal of arthrospira platensis with naturally intact three-dimensional helical structure demonstrating its desirable feasibility and efficiency in contaminant removal. [20][21][22] As an example, Doke's work showed that by using a spirulina strain they managed to remove up to 95% of biochemical oxygen demand, 52% of nitrate, and 76% of phosphate, while reducing the bacterial count up to75%. 23 As mentioned above, due to emulsifiers adhered to fluororesin microspheres, it is not possible for fluororesin microspheres to coagulate completely.…”
Section: Introductionmentioning
confidence: 99%